Transfer of agricultural work operation profiles to a tractor test stand for exhaust emission evaluation. (December 2018) - Ettl, Johannes; Bernhardt, Heinz; Pickel, Peter; Remmele, Edgar; Thuneke, Klaus; Emberger, Peter
Abstract : Exhaust gas emissions of combustion engines can be harmful to the environment, climate, and human health. Hence, emission limits have been increasingly reduced over the last few years, and new dynamic test cycles for test stands have been introduced. Recently, emission legislation was extended by adding testing procedures during real-world operations. The recording of so-called real driving emissions (RDE) with portable emission measurement systems (PEMS) is complex, especially for non-road applications, such as tractors. Emission-relevant sites and environmental conditions vary widely, and RDE measurements with PEMS are limited to an observation period of only a few hours. This paper presents a feasible methodology to determine exhaust emissions for specific tractor operations that are representative of longer periods. Based on long-term recorded GPS data, as well as engine control unit (ECU) speed and torque data from a tractor, six work-specific test cycles were developed and transferred to a tractor test stand. By comparing ECU data from test stand operations with ECU data recorded during field operations, the quality of the procedure was assessed. Emission measurements was conducted. Nitrogen oxides (NOX ), carbon monoxide (CO), hydrocarbons (HC), particulate matter (PM) and particulate number (PN) emissions for the tractor works considered with rapeseed oil (DIN 51605) and diesel fuel (CEC RF 06-03) were lower under real operation conditions than those when applying the legal non-road transient cycle (NRTC). The results show that using rapeseed oil fuel instead of diesel fuel offers a huge potential for reducing greenhouse gas emissions. Highlights: Six representative tractor test cycles are generated from 206 h of recorded ECU and GPS data. Successful replication of the in-field recorded engine operation profiles on the tractor test stand. Real work-based NOX, HC, CO and particle emissions are generally lower than those in legal-based test cycles. Rapeseed oil fuel features a high potential for greenhouse gas reduction.